Pengaruh Latihan Isometrik Bahu Dan Infrared Terhadap Pemulihan Kekuatan Otot Pada Pasien Post Orif Ekstermitas Atas Di Poli Orthopedi RSU Diponegoro Dua Satu Klaten - Dwi Astuti Nurnaningsih; Anik Suwarni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Upper extremity fractures treated with Open Reduction and Internal Fixation (ORIF) may cause several postoperative problems, including decreased muscle strength due to pain, immobilization, and limited movement. Isometric exercise and infrared therapy can be used as rehabilitative interventions to support muscle strength recovery. This study aimed to determine the effect of shoulder isometric exercise and infrared therapy on muscle strength recovery in post-ORIF patients with upper extremity fractures. This study employed a quantitative method with a pre-experimental one-group pretest-posttest design. The study was conducted from July to August 2026 at the Orthopedic Clinic of RSU Diponegoro Dua Satu Klaten. The sample consisted of 33 respondents selected using accidental sampling. Muscle strength was measured before and after the intervention using Manual Muscle Testing (MMT). Data were analyzed using the Wilcoxon Signed-Rank Test because the data were not normally distributed. Most respondents were aged 18–59 years (81.8%), female (66.7%), had a senior high school education (51.5%), and worked in the private sector (45.5%). Before the intervention, 54.5% had fair muscle strength and 45.5% had poor strength. After the intervention, 78.8% had fair, 12.1% good, and 9.1% poor muscle strength. The Wilcoxon test showed a significant difference in muscle strength before and after the intervention (p = 0.000 < 0.05), with the maximum score increasing from 3 to 4. The study concluded that shoulder isometric exercise and infrared therapy had a significant effect on muscle strength recovery in post-ORIF patients with upper extremity fractures at the Orthopedic Clinic of RSU Diponegoro Dua Satu Klaten. Shoulder isometric exercise and infrared therapy may be used as rehabilitative interventions to support muscle strength recovery in post-ORIF patients with upper extremity fractures.